2021
DOI: 10.1364/boe.426125
|View full text |Cite
|
Sign up to set email alerts
|

Computational multi-directional optical coherence tomography for visualizing the microstructural directionality of the tissue

Abstract: We demonstrate computational multi-directional optical coherence tomography (OCT) to assess the directional property of tissue microstructure. This method is the combination of phase-sensitive volumetric OCT imaging and post-signal processing. The latter comprises of two steps. The first step is an intensity-directional analysis, which determines the dominant en face fiber orientations. The second step is the phase-directional imaging, which reveals the sub-resolution depth-orientation of the microstructure. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The presence of muscle fiber crimps and a complex extracellular matrix may result in smaller anisotropy of polarization. In the angular distribution of structural orientation in optical coherence tomography, 37) it has been reported that the peak representing the degree of orientation is broader in chicken breast muscle than in Achilles tendon.…”
Section: Acoustically Induced Polarization Of Tendon and Musclementioning
confidence: 99%
“…The presence of muscle fiber crimps and a complex extracellular matrix may result in smaller anisotropy of polarization. In the angular distribution of structural orientation in optical coherence tomography, 37) it has been reported that the peak representing the degree of orientation is broader in chicken breast muscle than in Achilles tendon.…”
Section: Acoustically Induced Polarization Of Tendon and Musclementioning
confidence: 99%
“…For the experimental validation of VDC imaging, we used a fiber-based spectral-domain OCT system [13]. The light source was a superluminescent diode (SLD, Superlum, Ireland) with a center wavelength and bandwidth of 840 nm and 100 nm, respectively.…”
Section: System Samples and Image Acquisition Protocolmentioning
confidence: 99%
“…Oida et al demonstrated computational multi-directional (CMD)-OCT for qualitatively visualizing the microscopic phase structure of the sample [13]. This method exploits the phase angle of 𝑠(𝒙 + Δ𝒙/2)𝑠 * (𝒙 − Δ𝒙/2), and hence is similar to our VDC method.…”
Section: Defocusing Effect Of Computational Multi-directional (Cmd)-octmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is artifacts found in A-scan-wise Doppler OCT images caused by the structure of superior tissue. Another example relates to the specific imaging condition required for point-scanning computational multi-directional OCT [ 14 ]. In experiments, it was found that defocus is mandatory to achieve this method [ 15 ], but this necessity has not been explained in theory.…”
Section: Introductionmentioning
confidence: 99%